IMPLEMENTATION OF DIGITAL MARKETING PLAN TO INCREASE BRAND AWARENESS AND LLOILO TEA TURNOVER - Richart Richart; Golan Hasan (ConCEPt - Conference on Community Engagement Project, 2022)
The author does practical work on the LloiLo Tea SMME business starting on September 19 2021 until November 30 2021. The location of the LloiLo Tea SMME is located in Batu Aji. Mr. Sion Sihotang's micro, small and medium enterprises need a digital marketing plan to improve and face competition with other competitors. The author helps SMME owners to find obstacles and create strategies for businesses to be able to face other fierce competition.The process carried out during this practical work, the author conducted a survey and collected data for analysis in the form of the background of LloiLo Tea SMME. After doing the analysis, the author found several obstacles faced then the author implemented a strategy so that Mr. Sion Sihotang's business could compete with the current market. The obstacle found is the lack of a sales system so that it takes time to improve and develop a sales system. The system is a Digital marketing plan. Loilo Tea's micro, small and medium enterprises have implemented the results of the Digital Marketing Plan which was designed and developed by the author. The author has registered SMME with Go-Food partners, made advertisements posted on social media, namely Instagram, so that many consumers know what promotions are currently in effect on SMME LloiLo Tea.